Węgiel brunatny szansą dla społeczeństwa Województwa Lubuskiego = Brown coal opportunity for the public Lubuskie province - Chrzan, Tadeusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Are given and discussed the size of brown coal mining in Poland by 2040. From the analysis shows that a further deposit is exhausted and new mines to be run on new deposits. New dose of brown coal deposits are located in Lubuskie in the town of Gubin-Mosty-Brody. Energy produced from brown coal is the cheapest. It was fund that in the country have qualified personnel and which companies can build mines and needed machines.
Keywords: węgiel brunatny; kopalnie odkrywkowe; energia elektryczna; brown coal; brown coal mines; electricity